2019
DOI: 10.1371/journal.pone.0226348
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of machine learning methods in delta-radiomics feature analysis

Abstract: PurposeThis study aimed to investigate the effectiveness of using delta-radiomics to predict overall survival (OS) for patients with recurrent malignant gliomas treated by concurrent stereotactic radiosurgery and bevacizumab, and to investigate the effectiveness of machine learning methods for delta-radiomics feature selection and building classification models.MethodsThe pre-treatment, one-week post-treatment, and two-month post-treatment T1 and T2 fluid-attenuated inversion recovery (FLAIR) MRI were acquired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…Kebir et al carried out a similar analysis using 14 patients with HGG suspected of progression but used FET-PET imaging to identify 3 clusters based on 10 predominantly textural FET-PET features. Similar studies were also carried out by Chan et al and Petrova et al (64,65).…”
Section: Imaging and Response To Treatmentsupporting
confidence: 81%
See 1 more Smart Citation
“…Kebir et al carried out a similar analysis using 14 patients with HGG suspected of progression but used FET-PET imaging to identify 3 clusters based on 10 predominantly textural FET-PET features. Similar studies were also carried out by Chan et al and Petrova et al (64,65).…”
Section: Imaging and Response To Treatmentsupporting
confidence: 81%
“…The use of imaging to assess response to treatment in glioma is of tremendous importance for both patient management and outcome assessment. With respect to computational approaches on analyzing survival outcomes, research to date has focused on two main aspects: (i) distinguishing progression from pseudo-progression (62,63); and (ii) connecting systemic therapy or radiation therapy (RT) to imaging changes (64). Artzi et al utilized data generated using conventional, dynamic contrast enhanced (DCE)-MRI and magnetic resonance spectroscopy from 20 patients to extract the enhanced lesion area using independent component analysis and choline/creatine values and compared treatment-related changes with normal-appearing white matter.…”
Section: Imaging and Response To Treatmentmentioning
confidence: 99%
“…It is generally well-known that radiomic features are susceptible to scanner variation and inter-observer variability, 53 which can often lead to inconsistent downstream machine learning models. 54,55 To the best of our knowledge, our study is the first reported head and neck cancer radiomic analysis based on prospectively acquired intra-treatment 18 F-FDG-PET images and long-term clinical follow-up. Our findings are therefore strengthened by a highfidelity dataset representing a homogenous patient cohort without inter-scanner variability across different vendors, models, or acquisition protocols.…”
Section: Discussionmentioning
confidence: 93%
“…While most published radiomic studies rely on retrospective data, our results are based on a prospective clinical trial where all images were acquired on the same scanner under the same acquisition protocol. It is generally well‐known that radiomic features are susceptible to scanner variation and inter‐observer variability, 53 which can often lead to inconsistent downstream machine learning models 54,55 . To the best of our knowledge, our study is the first reported head and neck cancer radiomic analysis based on prospectively acquired intra‐treatment 18 F‐FDG‐PET images and long‐term clinical follow‐up.…”
Section: Discussionmentioning
confidence: 98%
“…For example, radiomic features extracted from the same tumor, pre-and post-treatment, show significant discrepancies (van Dijk et al, 2019). These ''delta'' features could be used to predict patient recurrence risk and late toxicity, helping to tailor followup plans (Chang et al, 2019). Appropriately triaging patients for escalated follow-up and attention can promote decreased morbidity and more efficient healthcare resource utilization; AI leveraging EHR data has demonstrated the ability to accomplish this by selecting patients at high risk for acute-care visit while undergoing cancer therapy and assigning them to an escalated preventive care strategy (Hong et al, 2020).…”
Section: T8 Follow-upmentioning
confidence: 99%